1999
DOI: 10.1016/s0735-1097(98)00575-0
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in myocardial blood flow dynamics

Abstract: These data suggest that the favorable lipid profile seen in women may be associated with preserved maximal blood flow in the myocardium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
43
2

Year Published

2001
2001
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(53 citation statements)
references
References 23 publications
8
43
2
Order By: Relevance
“…It has been demonstrated that women have higher HDL-C and lower TG compared to men in general population. 36 In this study we have detected the same pattern among individuals with SCI. Sex differences of the lipid profile suggests sex as a confounder and further analysis was performed with proper adjustments.…”
Section: Aminosupporting
confidence: 71%
“…It has been demonstrated that women have higher HDL-C and lower TG compared to men in general population. 36 In this study we have detected the same pattern among individuals with SCI. Sex differences of the lipid profile suggests sex as a confounder and further analysis was performed with proper adjustments.…”
Section: Aminosupporting
confidence: 71%
“…An earlier study attributed these higher MBFs to sex-related differences in lipid profiles. 17 Plasma lipid levels in our young women were, however, normal. Vasoactive effects of sex hormones may be one explanation, because all young women were studied during mid-cycle, when plasma levels of estrogen are high and of progesterone are low.…”
Section: Discussionmentioning
confidence: 55%
“…66,68,82,83 Although the causes of this sex difference are not completely defined, hormonal effects on coronary circulatory function in women with CAD, and sex-dependent lipid profile changes, may be important contributors. 66,68,82,83 Finally, in individuals with advanced obesity, resting MBF may also be elevated as induced by a more enhanced activation of the sympathetic nervous system and the renin-angiotensin-aldosterone axis, resulting in higher resting heart rate and arterial blood pressure. 70,83,84 Physiologic Ranges for MBF and MFR with 13 N-Ammonia and 82 …”
Section: Resting Mbfmentioning
confidence: 99%
“…66,68,82,83 Finally, in individuals with advanced obesity, resting MBF may also be elevated as induced by a more enhanced activation of the sympathetic nervous system and the renin-angiotensin-aldosterone axis, resulting in higher resting heart rate and arterial blood pressure. 70,83,84 Physiologic Ranges for MBF and MFR with 13 N-Ammonia and 82 …”
Section: Resting Mbfmentioning
confidence: 99%